Biotechnology, the gene revolution, and proprietary technology in agriculture: a strategic note for the World Bank - Dodds, J.H.; Ortíz, R.; Crouch, J.H.; Mahalasksmi, V.; Sharma, K.K. (2001)
The world economy experienced significant growth and transformation, with increases in productivity, product quality, and export base diversification in the 1990s. These advances were mainly driven by the growth of traditional agricultural and industrial sectors, including the natural resource-based sectors. This article outlines how application that New Science offers an opportunity for equitable growth that will assist in further poverty alleviation throughout the world. New Science will impact all poverty areas such as income, nutrition and environmental enhancement. The principal objective of this document was to provide a textual report on the topic of innovation in science and technology, and in particular the way that new science such as biotechnology and information technology serve as factors for increasing the competitiveness of developing nations in the global context. Interwoven into this subject matter the report provides clear positions to consider adopting in the critical areas of Intellectual Property Rights, Biotechnology Biosafety, Trade and Environmental Protection.